2020
DOI: 10.3390/molecules25173922
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Neuroprotective Response of Thioredoxin Reductase against Oxidative-Nitrosative Stress Induced by Experimental Autoimmune Encephalomyelitis in Rats: Modulation by Theta Burst Stimulation

Abstract: Cortical theta burst stimulation (TBS) structured as intermittent (iTBS) and continuous (cTBS) could prevent the progression of the experimental autoimmune encephalomyelitis (EAE). The interplay of brain antioxidant defense systems against free radicals (FRs) overproduction induced by EAE, as well as during iTBS or cTBS, have not been entirely investigated. This study aimed to examine whether oxidative-nitrogen stress (ONS) is one of the underlying pathophysiological mechanisms of EAE, which may be changed in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…The effect of the CTBS noise artifact was explored in the sham group of animals (EAE+CTBSpl), which were subjected to the noise artifact according to the same experimental scheme. Significant reduction in duration, disability, and weight loss were observed after CTBS treatment, compared to both sham and naïve animals, as previously published (Figure 2) [37,39].…”
Section: The Effect Of Continuous Theta-burst Stimulation On the Dise...supporting
confidence: 86%
See 1 more Smart Citation
“…The effect of the CTBS noise artifact was explored in the sham group of animals (EAE+CTBSpl), which were subjected to the noise artifact according to the same experimental scheme. Significant reduction in duration, disability, and weight loss were observed after CTBS treatment, compared to both sham and naïve animals, as previously published (Figure 2) [37,39].…”
Section: The Effect Of Continuous Theta-burst Stimulation On the Dise...supporting
confidence: 86%
“…Up to date, the efficacy of different TBS protocols has been explored in animal studies using EAE, as an experimental paradigm of RRMS. The studies have demonstrated reduced oxidative stress [37,38], attenuation of gliosis [39], and increased expression of brain-derived neurotrophic factor (BDNF) [40]. Therefore, the present study aims to explore the effect of continuous theta-burst stimulation (CTBS) protocol on purinergic system activity in the context of neuroinflammation associated with experimental autoimmune encephalomyelitis in Dark Agouti rats.…”
Section: Introductionmentioning
confidence: 98%
“…Inflammatory phenomena are tightly coupled with the overproduction of reactive oxygen and nitrogen species, which may produce neuronal degeneration. Improvement in oxidative status following iTBS, and its antioxidative potential ( Medina-Fernández et al, 2018 ; Stevanovic et al, 2020 ) could be mediated via nuclear factor (erythroid-derived 2)-like 2 (Nrf2) that is involved in transcriptional regulation of antioxidative enzymes ( Jaiswal, 2004 ). Previous studies reported that TMS increases the expression of Nrf2 in neuroinflammatory conditions ( Tasset et al, 2013 ; Liang et al, 2021 ), which could also be the mechanism in TMT-mediated oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress was assessed by measuring several parameters in appropriate hippocampal fraction ( n = 4–5 animals/group) as described in detail elsewhere ( Stevanovic et al, 2020 ). Briefly, total superoxide dismutase activity (tSOD) was assessed by spectrophotometric determination of spontaneous epinephrine autooxidation decrease rate at 480 nm and expressed as units per milligram of total protein (U/mg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation